Genetic analysis of the ADGF multigene family by homologous recombination and gene conversion in Drosophila. - Dolezal, T.; Gazi, M.; Zurovec, M.; Bryant, P.J. (Genetics, 2003)
Many Drosophila genes exist as members of multigene families and within each family the members can be functionally redundant, making it difficult to identify them by classical mutagenesis techniques based on phenotypic screening. We have addressed this problem in a genetic analysis of a novel family of six adenosine deaminase-related growth factors (ADGFs). We used ends-in targeting to introduce mutations into five of the six ADGF genes, taking advantage of the fact that five of the family members are encoded by a three-gene cluster and a two-gene cluster. We used two targeting constructs to introduce loss-of-function mutations into all five genes, as well as to isolate different combinations of multiple mutations, independent of phenotypic consequences. The results show that (1) it is possible to use ends-in targeting to disrupt gene clusters; (2) gene conversion, which is usually considered a complication in gene targeting, can be used to help recover different mutant combinations in a single screening procedure; (3) the reduction of duplication to a single copy by induction of a double-strand break is better explained by the single-strand annealing mechanism than by simple crossing over between repeats; and (4) loss of function of the most abundantly expressed family member (ADGF-A) leads to disintegration of the fat body and the development of melanotic tumors in mutant larvae.